Recent Update on Various Ion Doped Nanoparticles Applied in Biomedical: Challenges and Future Perspective - Aldi Herbanu; Sjaikhurrizal El Muttaqien; Muhammad Artha Jabatsudewa Maras (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
In the last several years, there have been a considerable increase in the number of use of nanoparticles (NPs) in dental application. For application and study, a wide range of ion doped NPs are accessible. The NPs differ from conventional materials in term of their distinctive structures and properties. However, researchers don't always understand how these NPs with their unique properties work. The NPs foundation in material science as well as benefits and drawbacks are discussed, primarily based on a review of the most cited scientific papers in the international peer-reviewed journal sciences. To meet the requisite topic of the study, 22 titles from MEDLlNE (PubMed) databases and 145 titles from the Scopus database were screened. It was determined from the included papers that this review takes into account several facets of the preparation of different ions for doping dental NPs and their therapeutic uses of doped hydroxyapatite (HAP). Understanding the physical, chemical, and biological aspects of NPs may help us to comprehend their benefits, drawbacks, and particular advantages. Although NPs offer great potential for the future, they do not necessarily have the best qualities, particularly in the biomedical field.Keywords: Ions-doped; bone remodeling; doped hydroxyapatite; nanoparticles; regenerative therapy